2022
DOI: 10.3389/fphys.2022.966454
|View full text |Cite
|
Sign up to set email alerts
|

An integrated proteomic and transcriptomic signature of the failing right ventricle in monocrotaline induced pulmonary arterial hypertension in male rats

Abstract: Aim: Pulmonary arterial hypertension (PAH) is an obstructive pulmonary vasculopathy that results in death from right ventricular failure (RVF). There is limited understanding of the molecular mechanisms of RVF in PAH.Methods: In a PAH-RVF model induced by injection of adult male rats with monocrotaline (MCT; 60 mg/kg), we performed mass spectrometry to identify proteins that change in the RV as a consequence of PAH induced RVF. Bioinformatic analysis was used to integrate our previously published RNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
(138 reference statements)
1
3
0
Order By: Relevance
“…In 2021, Park et al [10] reported that the end-stage transcriptomic signatures between SuHx and MCT rats were moderately similar (2693 common genes; 34% of the differentially expressed MCT genes; 86% of the differentially expressed SuHx genes). The genes they identified as being important in RV remodeling were in broad agreement with previous RV gene-expression studies of both MCT [27,28] and SuHx [29] rats, and most of the genes found for MCT rats have also been reported as differentially expressed at the protein level [27].…”
Section: Acute Vs Gradual Increase In Rv Pressure Overload: Can Pab O...supporting
confidence: 86%
“…In 2021, Park et al [10] reported that the end-stage transcriptomic signatures between SuHx and MCT rats were moderately similar (2693 common genes; 34% of the differentially expressed MCT genes; 86% of the differentially expressed SuHx genes). The genes they identified as being important in RV remodeling were in broad agreement with previous RV gene-expression studies of both MCT [27,28] and SuHx [29] rats, and most of the genes found for MCT rats have also been reported as differentially expressed at the protein level [27].…”
Section: Acute Vs Gradual Increase In Rv Pressure Overload: Can Pab O...supporting
confidence: 86%
“…Because Fatty Acid Oxidation (FAO) and ETC pathways were identified in our porcine analysis and alterations in these pathways are present in human heart failure(23,24), we evaluated and compared the relative changes in FAO and ETC in rodents (GSE119754, PXD027273), pigs, and humans (GSE198618) (10,11,25). In the proteomics analysis, abundances of nearly all FAO and ETC proteins were reduced in MCT rats as compared to control rats ( Figure 6A-B ).…”
Section: Resultsmentioning
confidence: 99%
“…As we can see, proteins involved in the same pathway tend to form a tight interaction with each other. Recent proteomic analysis on the RV from MCT-induced PAH model rats was reported by three groups, Hołda et al, 8 Qin et al, 7 and Hindmarch et al 22 Several upregulated proteins were identified in our study, including Postn, Nppa, Hmox1 (heme oxygenase 1), Plod2 (procollagen-lysine 5-dioxygenase), and Gpnmb (glycoprotein nmb), also noted by Hindmarch et al In addition to these five proteins, the upregulation of several other hypertrophy or heart failure-associated proteins was further validated using qRT-PCR, including Fstl1, Ltbp2, and Ncam1. This consistency underscores the reliability of our proteomic analysis.…”
Section: Protein−protein Interaction Network Analysis For Significant...mentioning
confidence: 99%